Gender, responsible citizenship and global climate change. (May 2015) - Salehi, Sadegh; Pazuki Nejad, Zahra; Mahmoudi, Hossein; Knierim, Andrea
Synopsis: Public participation in climate change policy requires a clear understanding of the issues. This is essential if an informed society is to achieve the goal of reducing greenhouse gas emissions and adapt to climate change. Women, due to the type of activities they perform in the household, may have a prominent and leading role in this sphere and thus constitute a group holding great potential to support policies to deal with adaptation to climate change. The purpose of the present study is to assess gender-related awareness of climate change issues and the engagement of citizens in climate change mitigation based on eco-feminism theory to the socio-cultural features of citizen households in Iran. To this end, 310 residents of Quemshahr in Mazandaran province (Iran) were selected with a random sampling method. The results show that while women's behavioral engagement in tackling climate change is high, men exhibit a high level of cognitive dimension of engagement in tackling climate change. Furthermore, the results show that the level of citizens' engagement varies by education and age. Based on the research findings, activities to promote environmental education and understanding of climate change mitigation policies are proposed to increase the level of knowledge of the target group.